Digital Ethics and Legal Responsibility of Digital Platform Providers in Controlling Illegal Content in Indonesia - Perdana, Rizqi Surya (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The rapid growth of the digital ecosystem has created a number of ethical and legal challenges for both the state and Electronic System Operators (ESOs), especially in preventing and handling illegal content. Indonesia has tried to respond to these changes through a set of rules that lean heavily toward security and public order, such as the Electronic Information and Transactions Law, Government Regulation No. 71 of 2019, and Ministrial Regulation No. 5 of 2020. These laws give the government broad authority to order swift takedowns of online content and place ESOs at the front line of maintaining a safe and responsible digital environment. However, the problem is not simply about how fast content can be removed. A bigger issue is the scattered and sometimes overlapping nature of Indonesia’s regulations, which are spread across various sectoral frameworks. This regulatory fragmentation leads to different standards, confusion for platforms, and uncertainty for users. It also affects the broader issues about digital ethics. The European Union approaches content governance differently, emphasizing transparency, accountability, and clear procedures. The DSA requires platforms to provide user appeal mechanisms, undergo independent audits, and disclose systemic risks. Meanwhile, the United States takes a more hands-off approach. This article employs a normative legal method, combining statutory and comparative approaches to achieve a more holistic result. The findings show that Indonesia continues to place the government at the center of content control, relying on strict, rapid takedown requirements. Yet issues such as regulatory fragmentation, limited transparency in algorithms, lack of clear appeal rights, and uncertainties around non-discrimination remain largely unresolved. Compared to the EU and US models, it’s clear that Indonesia needs a more balanced framework, one that protects public interests without overlooking platform responsibilities or the digital rights of its citizens.